Limits on performance and survival of juvenile sockeye salmon (Oncorhynchus nerka) during food deprivation: a laboratory-based study. Issue 1 (24th March 2021) - Wilson, Samantha M; Robinson, Kendra A; Gutzmann, Sarah; Moore, Jonathan W; Patterson, David A
Abstract : Sockeye salmon smolts can undergo vast migrations without feeding. We explored relationships between deteriorating body condition and swim performance/survival. Most fish could not complete a swim challenge after 3 weeks without food, and after 8 weeks, 50% had perished. Condition factor and energy density predicted swim performance and survival, respectively. Abstract: Long-distance migrations can be energetically demanding and can represent phases of high mortality. Understanding relationships between body condition and migratory performance can help illuminate the challenges and vulnerabilities of migratory species. Juvenile anadromous sockeye salmon ( Oncorhynchus nerka ) may migrate over 1000 km from their freshwater nursery habitats to estuary and ocean feeding grounds. During the period corresponding to the seaward migration of sockeye salmon, we held smolts in the laboratory to ask the following: (i) Does non-feeding migration duration influence prolonged swim performance and survival? (ii) What are the relationships between individual body condition and swim performance and survival? Wild sockeye salmon were intercepted during their migration and held without food for up to 61 days to represent the non-feeding freshwater migration and the extremes of poor estuary habitat. We conducted 40 sets of prolonged swim trials on 319 fish from 3 treatment groups that represented entrance to the marine environment on (i) an average, (ii) a delayed and (iii) a severely delayed migration schedule. Experimentally controlled freshwater migration duration did not impact swim performance or survival. Swim performance decreased concomitant with condition factor, where smolts with a Fulton's condition factor of <0.69 were less likely (<50% probability) to complete the swim test (90 min swim test, at 0.50 m/s). Survival of salmon smolts in the laboratory was less likely at energy densities of less than 3.47 MJ/kg. Swim performance decreased much sooner than survival, suggesting that swim performance, and therefore condition factor, may be a good indicator of survival of migratory smolts, as fish with reduced swim performance will likely be predated. These two relationships, one more ecologically relevant and one more clinical, help reveal the limits of long-distance migration for juvenile salmon and can be used to determine population-specific starvation risk associated with various freshwater and marine habitat conditions.